Analisa Kandungan Salmonella sp Pada Telur Mentah dan Telur Setengah Matang Pada Warung Kopi Di Jalan Samanhudi Kelurahan Hamdan Kecamatan Medan Maimun Tahun 2013 - Dody usman; taufik ashar; evi naria (Lingkungan dan Kesehatan Kerja, 2014)
Egg in half cooked food prepared by boiling an egg approximately 5 minutes in order to get high protein from the eggs. Eggs can contain bacteria harmful food called Salmonella sp. Because of that the authors consider it necessary to conduct research on analysis of Salmonella sp. the food half cooked eggs. The purpose of this study is to find out about the analysis of Salmonella sp. the food half-cooked eggs are sold in the village Samanhudi Hamdan Maimoon Medan Medan District. The method used in this study is a descriptive to see observations and laboratory analysis to determine the content of the bacteria Salmonella sp. the food half cooked eggs. The results showed that in a sample of 10 egg mixture before brewed with hot water, 2 of 10 samples found to be contaminated with Salmonella sp eggs. Meanwhile, mix eggs for 10 samples, after brewed with hot water, discovered the bacterium Salmonella sp. Sp salmonella bacteria content in food is expected to meet the standards that refer to SNI 01-6366-2000 that is negative or zero (0). The conclusion of this study indicate that the bacterial content in foods by processing existing health ineligible because eggs contain bacteria that were previously brewed still contain bacteria after Salmonella sp. Eggs containing bacteria probably caused long storage and processing methods that do not meet the standards. The expected need for supervision and counseling to the holding of merchants by the local government on the importance of food processing eggs and to increase efforts to restructure the food so that the food received eggs already qualified healthcare consumers. Keywords: Half-cooked Eggs, Salmonella sp.